Cover Image. Issue 4 (20th August 2020) - Unknown
Abstract : Using reactive force‐field based molecular dynamics simulation, Nilanjan Mitra and colleagues in the article e10143, study stretch‐induced helix to extended coil transition in crystalline α‐isotactic polypropylene. The helix to coil transition was observed prior to the breaking of the backbone carbon chain. The cover image features a helical representation of a single helical chain of crystalline α‐isotactic polypropylene, along with the stress‐strain plots, initial crystal structure, and structure after chain breakage with the evolution of the dihedral, helix radius, and pitch length. (doi.org/10.1002/pcr2.10143 ) Abstract : Using reactive force‐field based molecular dynamics simulation, Nilanjan Mitra and colleagues in the article e10143, study stretch‐induced helix to extended coil transition in crystalline α‐isotactic polypropylene. The helix to coil transition was observed prior to the breaking of the backbone carbon chain. The cover image features a helical representation of a single helical chain of crystalline α‐isotactic polypropylene, along with the stress‐strain plots, initial crystal structure, and structure after chain breakage with the evolution of the dihedral, helix radius, and pitch length. (doi.org/10.1002/pcr2.10143 )